Proceedings of the 6th International Systems and Storage Conference on - SYSTOR '13 2013
DOI: 10.1145/2485732.2485754
|View full text |Cite
|
Sign up to set email alerts
|

Examining extended and scientific metadata for scalable index designs

Abstract: While file system metadata is well characterized by a variety of workload studies, scientific metadata is much less well understood. We characterize scientific metadata, in order to better understand the implications for index design. Based on our findings, existing solutions for either file system or scientific search will not suffice for indexing a large scientific file system.We describe the problems with existing solutions, and suggest column stores as an alternative approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…With the explosively growing size of data storage systems, some recent studies [16,17] collect and analyze characteristics of various system workloads in practical application. From these studies, some new features of the file metadata are found.…”
Section: File Metadata and Metadata Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…With the explosively growing size of data storage systems, some recent studies [16,17] collect and analyze characteristics of various system workloads in practical application. From these studies, some new features of the file metadata are found.…”
Section: File Metadata and Metadata Searchmentioning
confidence: 99%
“…The R-tree has been the most popular spatial index structure, and it is more suitable for indexing multi-dimensional attributes than B-tree [7,17]. X-tree is a variant of the R-tree.…”
Section: Overhead Of Metadata Searchingmentioning
confidence: 99%
“…As ever increasing volumes of data (which some call the digital landfill) are generated, it becomes nearly impossible to store and retrieve data with a single computer. The management of large volumes of astronomical FITS data files is beyond the scope of traditional data indexing technologies (Greisen et al 1981;Gray et al 2005;Parker-Wood et al 2013). Thus, NoSQL technology was presented, offering a timely alternative to the object-relational data model.…”
Section: Related Workmentioning
confidence: 99%
“…The study of [18] proposes an architecture that uses a column store as a basis for a lazy index. In this process, fields are stored, unprocessed, embedded in the data until the first query is issued.…”
Section: Other Studies On Fast Data Processingmentioning
confidence: 99%